Implementation of Child-Friendly School in the Perspective of Islamic Religious Education in Elementary Schools in North Kalimantan - Muhammad Arbain; Gusniati, Yeisi; Tamam, Badrut; Fadilah, Nurul; Syaiful (IAIN PAREPARE, 2024)
Background : Cases of physical and non-physical violence against children in schools are increasing, violating legal, social, cultural, and religious norms. In response, the Ministry of Education and Culture launched the Child-Friendly School initiative to create an educational environment prioritizing safety, comfort, and inclusivity. Islamic religious education aligns with this initiative by emphasizing moral behavior, respect, and prohibiting harmful actions such as bullying and discrimination. Research objectives: This study aims to formulate the concept of implementing child-friendly schools from the perspective of Islamic religious education in elementary schools in North Kalimantan. Methods: Using a qualitative descriptive method, data were collected through observations, interviews, and documentation involving 10 school principals, 15 Islamic religious education (PAI) teachers, and 30 students from elementary schools in Bulungan, Tarakan, and Tana Tidung regions. The findings reveal six main elements: (1) conducive and religious learning atmosphere, (2) adequate facilities, (3) exemplary and quality teachers, (4) integration of local cultural content in the curriculum, (5) a safe and peaceful school environment, and (6) active involvement of parents and school committees. Conclusion: A combination of Islamic teachings and local cultural wisdom fosters a holistic child-friendly school model. The integration of Islamic values with child-friendly school principals enhances inclusivity and emotional well-being. This study introduces a context-specific integration of religious and cultural values into child-friendly school frameworks. Theoretically, it expands the understanding of child-friendly education through an Islamic perspective. Practically, it offers actionable guidelines for sustainable implementation. Socially, it emphasizes collaboration between schools, parents, and communities.